A prospective study of dietary patterns and the incidence of endometriosis diagnosis - Dougan, Marcelle M.; Fest, Sable; Cushing-Haugen, Kara; Farland, Leslie V.; Chavarro, Jorge; Harris, Holly R.; Missmer, Stacey A. (American journal of obstetrics and gynecology, 2024)
Although endometriosis is a common condition—affecting ∼10% of premenopausal individuals—its etiology is unknown. Diet receives a lot of attention from patients, but studies of the role of diet are limited. Examining dietary patterns is essential to provide new insight. We sought to determine whether dietary patterns are associated with laparoscopically-confirmed endometriosis diagnosis. We conducted a prospective cohort study among 81,997 premenopausal participants of the Nurses’ Health Study II, who were followed from 1991–2015. Diet was assessed with validated food frequency questionnaires every 4 years. We examined 6 dietary patterns: Western, Prudent, Alternative Healthy Eating Index, Dietary Approaches to Stop Hypertension, an estrogen-associated pattern, and a proinflammatory pattern. Cox proportional hazard ratios and 95% confidence intervals were used to quantify the association between each of these patterns and laparoscopically-confirmed endometriosis diagnosis. Three thousand eight hundred ten incident cases of endometriosis were diagnosed during 24 years of follow-up. Adherence to the Alternative Healthy Eating Index, reflecting a healthier dietary pattern, was associated with a 13% lower risk of endometriosis diagnosis (fifth vs first quintile 95% confidence interval, 0.78–0.96; Ptrend=.02). Participants in the highest quintile of the Western dietary pattern, characterized by high intake of red meat, processed meat, refined grains, and desserts, had a 27% higher risk of endometriosis diagnosis than those in the lowest quintile (95% confidence interval, 1.09–1.47; Ptrend=.004). The Prudent, Dietary Approaches to Stop Hypertension, and estrogen-associated dietary patterns did not demonstrate clear associations with endometriosis risk, and there was the suggestion of a higher risk of endometriosis diagnosis among those with a higher proinflammatory diet score (hazard ratio for fifth vs first quintile, 1.10 [95% confidence interval, 0.99–1.23]; Ptrend=.01). Our results suggest that consuming a dietary pattern that adheres to the Alternative Healthy Eating Index-2010 recommendations lowers the risk of endometriosis diagnosis, potentially through a beneficial impact on pelvic pain. In addition, consuming a less healthy diet high in red/processed meats and refined grains may have a detrimental impact on endometriosis symptoms.